2014
DOI: 10.3390/toxins6072082
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific Variation of Centruroides Edwardsii Venom from Two Regions of Colombia

Abstract: We report the first description studies, partial characterization, and intraspecific difference of Centruroides edwardsii, Gervais 1843, venom. C. edwardsii from two Colombian regions (Antioquia and Tolima) were evaluated. Both venoms showed hemolytic activity, possibly dependent of enzymatic active phospholipases, and neither coagulant nor proteolytic activities were observed. Venom electrophoretic profile showed significant differences between C. edwardsii venom from both regions. A high concentration of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 43 publications
4
16
1
2
Order By: Relevance
“…This activity is confirmed as dependent on the presence of PLA 2 since the complete venom and two fractions eluting at 51.8 and 57.5 min hydrolyzed the specific substrate 4-nitro-3-octanoyloxy-benzoic acid. The electrophoretic and chromatographic profile confirms the presence of compounds with similar molecular masses of these phospholipases, bands around 14 kDa, and different peaks eluted in the arachnids’ phospholipase region, between 25% and 30% acetonitrile, as described in different arachnids [ 16 , 29 , 30 , 31 ]. More specific assays should be performed to determine enzymatic parameters and characterize these enzymes.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This activity is confirmed as dependent on the presence of PLA 2 since the complete venom and two fractions eluting at 51.8 and 57.5 min hydrolyzed the specific substrate 4-nitro-3-octanoyloxy-benzoic acid. The electrophoretic and chromatographic profile confirms the presence of compounds with similar molecular masses of these phospholipases, bands around 14 kDa, and different peaks eluted in the arachnids’ phospholipase region, between 25% and 30% acetonitrile, as described in different arachnids [ 16 , 29 , 30 , 31 ]. More specific assays should be performed to determine enzymatic parameters and characterize these enzymes.…”
Section: Discussionsupporting
confidence: 64%
“…The induced ataxia and indirect death was due to the low concentration of the fraction collected from the RP-HPLC. Insecticidal activity has been widely reported in other Phoneutria genera especially in P. nigriventer where the Tx4 family toxins have been identified as responsible for this activity [ 19 ] along with other different arachnids such as the scorpion Centruroides edwardsii [ 29 ]. This activity is most probably mediated through actions in the glutamatergic synapses in the neuromuscular junctions [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Con base en los resultados descritos, es posible concluir que el componente peptídico del veneno de T. macrochirus tuvo actividad citotóxica en las líneas celulares evaluadas, lo cual se ha observado también en péptidos purificados y sintetizados a partir de otros venenos de escorpión, por lo cual se han empezado a considerar como una alternativa para el diseño y la elaboración de nuevos agentes terapéuticos (13,16,18,(43)(44)(45)(46)(47)(48)(49)(50)(51). De ahí la necesidad de separar completamente algunos de los péptidos de este veneno y evaluar el efecto que cada uno de ellos produce en las diferentes líneas celulares evaluadas para determinar plenamente el responsable de cada uno de los efectos observados.…”
Section: Discussionunclassified
“…This study indicated that less of the variation within a species may be partly attributed to the high mobility of these flies. Such variability in larger geographical distributions may be attributed to diverse factors, such as age, gender, type of food, environmental conditions, genetic diversity, and geographic location (Estrada-Gomez et al, 2014).…”
Section: Phylogenetic Relationships Based On Coi Genementioning
confidence: 99%